Tradisi Wetonan Pada Suku Jawa Sebagai Perhitungan Kelahiran Anak di Desa Sei Simujur Kabupaten Batu Bara - Aulia, Cyndy; Dora, Nuriza (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research focuses on "Wetonan Tradition in Javanese Culture as a Method for Calculating Childbirth in Sei Simujur Village, Batu Bara Regency". It generally examines and analyzes the practices and significance of the Wetonan tradition in Javanese society. The study specifically delves into how the Wetonan tradition is used as a method for calculating childbirth and how it influences family decision-making regarding childbirth, parenting, and the future plans for children in Sei Simujur Village. The research aims to provide an in-depth understanding of how the Wetonan tradition affects the daily lives of the local community and its role in shaping family decisions related to childbirth. The research methodology involves a qualitative approach through in-depth interviews and participatory observation. The research findings reveal that the Wetonan tradition is not merely a calculation system based on the Javanese calendar but also reflects the richness of the belief system and cultural values inherent in Javanese society. The Wetonan tradition plays a crucial role in shaping parenting practices, education, and future planning for children in Javanese families in Sei Simujur Village. This study contributes significantly to the understanding of local cultural heritage and the dynamics of Javanese community life. It is hoped that the findings of this research will provide new insights into the importance of preserving traditional culture in the era of modernization and globalization. The research is also expected to provide guidance for policymakers to support the preservation of local culture and sustainable development in the Sei Simujur Village and surrounding areas.